2021
DOI: 10.18332/ejm/140139
|View full text |Cite
|
Sign up to set email alerts
|

What are the factors affecting parents’ postnatal sense of security?

Abstract: INTRODUCTION The postpartum period is part of an important process for mothers and fathers. A sense of security is central as it might influence a parent's journey towards becoming a successful parent. The aim was to determine factors affecting parents' postnatal sense of security (PPSS) before postpartum discharge from a hospital in Konya, Turkey. METHODS A descriptive study was conducted. From January 2019 to March 2019, a questionnaire was given to a convenience sample of 188 couples discharged from a regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
1
1
2
Order By: Relevance
“…Some authors state that monitoring pregnancy can be translated into feelings of tranquillity when mother and baby are physically well, which triggers feelings of security in this phase and in subsequent ones, such as childbirth and at postpartum. 1,18 On the other hand, and contrary to other studies, no statistically significant relationship was identified between being prepared for parenthood and the perception of security at postpartum. Preparation for parenthood has become an integral part of pregnancy monitoring in health care in Portugal.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Some authors state that monitoring pregnancy can be translated into feelings of tranquillity when mother and baby are physically well, which triggers feelings of security in this phase and in subsequent ones, such as childbirth and at postpartum. 1,18 On the other hand, and contrary to other studies, no statistically significant relationship was identified between being prepared for parenthood and the perception of security at postpartum. Preparation for parenthood has become an integral part of pregnancy monitoring in health care in Portugal.…”
Section: Discussioncontrasting
confidence: 93%
“…One of the studies points to women who gave birth vaginally as having a higher perception of security at postpartum. 18 Cesarean section is a surgical procedure that inevitably carries more maternal and perinatal risks when compared to vaginal delivery and, as such, is likely to be associated with higher levels of maternal anxiety and insecurity. 21 Other authors also add the first skin-to-skin contact between mother and child as a contributing factor to a positive childbirth experience.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns autores afirmam que a vigilância da gravidez pode ser traduzida em sentimentos de tranquilidade quando a mãe e o bebê apresentam bem-estar físico, o que despoleta sentimentos de segurança nesta fase e nas subsequentes, como o parto e o pós-parto. 1,18 Por outro lado, e contrariamente a outros estudos, não foi identificada uma relação com significado estatístico entre ter feito preparação para a parentalidade e a percepção de segurança no pós-parto. A preparação para a parentalidade tem vindo a ser parte integrante do acompanhamento da gravidez nos cuidados de saúde em Portugal.…”
Section: Discussionunclassified
“…Um dos estudos aponta as mulheres com partos vaginais como sendo aquelas com maior percepção de segurança no pós-parto. 18 A cesariana é um procedimento cirúrgico que, inevitavelmente traz mais riscos maternos e perinatais, quando comparada ao parto vaginal e, como tal, é passível de ser associada a níveis superiores de ansiedade e insegurança materna. 21 Outros autores, acrescentam ainda o primeiro contacto pele-a-pele entre mãe e filho como fator contribuinte para uma experiência positiva de parto.…”
Section: Discussionunclassified